Functional connectivity in distributed cortical networks associated with semantic processing in healthy older adults - Langer, Kailey G.; O’Neal, Alexandria G.; Garcia, Amanda; Chen, Alexa; Porges, Eric C.; Williamson, John B.; Woods, Adam J.; Cohen, Ronald A. (Frontiers in Aging Neuroscience, 2025)
ObjectiveWhile word knowledge is typically well-preserved in aging, declines in executive control often observed in older adults may impact access and application of this knowledge. Evidence suggests aging is associated with declines in specialization and efficiency of pre-defined cortical networks, potentially corresponding with cognitive changes. Building upon our previous findings that delineate task-relevant semantic network activation, this study investigates connectivity patterns in additional higher-order cortical networks during a semantic association task in cognitively healthy older adults.MethodsA total of 33 older adults (61% women, 94% White, aged 70.03 ± 11.28, 16.36 ± 2.62 years of education) completed task-based functional MRI involving semantic (abstract and concrete) and phonemic (rhyming) decisions. Networks included cingulo-operculate (CON), frontal-parietal control (FPCN), default mode (DMN), dorsal attention (DAN), and a semantic network. Association between block and intra-network connectivity was assessed. If block effects were found, ROI-ROI analysis was conducted. Additionally, inter-network correlations to age were examined, along with inter-network connectivity based on task demand.ResultsAge was not associated with intra-network connectivity. Semantic network connectivity increased during semantic blocks relative to rhyme. DAN and DMN connectivity increased during rhyme relative to semantic blocks, especially for abstract words. Connectivity within other networks did not differ as a function of task demands. Inter-network connectivity strength was stronger for FPCN with DAN during the rhyme blocks, and weaker during the rhyme blocks for FPCN with DMN and DMN with DAN. Older age was associated with greater inter-network connectivity for DMN with both FPCN and CON. The semantic network evidenced less intra-network connectivity during the rhyme task compared with all other networks, and greater intra-network connectivity during abstract semantic decisions compared with DAN and DMN.ConclusionDespite trends of decreased functional specialization in aging, and prior evidence within this cohort of broad task-related activation and connectivity bilaterally, semantic task relevance remained uniquely localized to left hemisphere semantic network hubs. Increased coherence within DAN and DMN during rhyme blocks may reflect novelty of the rhyming task, underscoring flexible network recruitment for demanding tasks in healthy aging. Findings contribute to our understanding of underlying neural mechanisms involved in semantic processing in cognitive aging.